Perbandingan Penambahan Limbah Serbuk Kayu Sebagai Pengganti Sebagian Agregat Halus Dan Penggunaan SikaFume® Terhadap Kuat Tekan Beton - Zulkarnain, Fahrizal; Parinduri, Rezi Six Rullah (Jurnal TESLINK : Teknik Sipil dan Lingkungan, 2024)
ABSTRACT Sawdust left over from sawmills is a common sight in every wood processing company. So far, sawdust waste processing has not been utilized optimally. Unused saw shavings are usually thrown away or burned while there exist several mankind whosoever disare to use the used sawdust to make tinder. This study shows that using extra materials such as sawdust and sycamore is intended to expansion the compressive strength of the concrete. Such research focus understand the comparison of compressive strength of concrete combined with sawdust and concrete combined with sawdust and sikafume. This research uses sawdust with a difference of 1% and 2% of the load of sand and the reckoning 5% a few load of cement. Cylinder parameters ∅= 15 cm and t = 30 cm. The combination concept applies SNI 7656:2012 steps. Three samples were made for each difference, so there were a total of 18 samples. The test applied is compressive strength of concrete. The maximum compressive strength results in 28 days were achieved in concrete with a combination of 2% sawdust + 5% sikafume, namely 21.81 MPa, experiencing an expansion in the compressive strength value of 9.4% beginning with normal concrete, namely 1.87 MPa, and sawdust concrete experienced The decrease in concrete with a mixture of sawdust + sikafume was 21.6%, namely 4.71 MPa. Keyword : Sawdust, SikaFume®, compressive strength